Studi Kasus sebagai Strategi Riset untuk Mengembangkan Akuntansi Sektor Publik - Mahmudi Mahmudi (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2003)
It is undoubtedly recognized that research has an important role in developing theories and practices towards a certain discipline. The existence of a science will stagnate or may disappear without any continuous research, basic or applied research. Public sector accounting theory is less developed compared to the business accounting theory. Because the nature and characteristic of public sector accounting are different from commercial accounting, the research method should be fitted according to its nature. Case study as a preferred research strategy seems very fit for the development of public sector accounting theories and practices. This article, firstly explores various philosophical approaches of research methodology and their effects on accounting research. The article also discusses about the development stage of accounting research, and the role and benefit of case study research in the development of public sector accounting.Keywords: Case Study, Research Methods, Grounded Research, and Theory Development.